Retention of perylene diimide optical properties in solid-state materials through tethering to nanodiamonds. Issue 32 (2nd August 2021) - Almuhana, Asia R. Y.; Langer, Philipp; Griffin, Sarah L.; Lodge, Rhys W.; Rance, Graham A.; Champness, Neil R.
Abstract : Nanodiamond-perylene diimide composites retain solution phase optical properties of the parent perylene diimide dye in the solid state. Abstract : The synthesis of nanodiamond-perylene diimide composites is reported. Suitably hydroxyl-functionalised perylene diimides (PDIs) are reacted with carboxylic acid functionalised nanodiamonds (NDs) through ester formation. The ND-PDI nanocomposite materials were characterised using a variety of different techniques confirming retention of the ND cores and interestingly the dye properties of the PDIs. In particular, fluorescence measurements suggest that PDIs tethered to NDs retain the characteristics of solution-phase PDIs rather than the optical properties associated with solid-state PDIs which are typically modified due to aggregation. Our relatively simple approach provides a mechanism for maintaining the solution-phase properties of PDIs in solid-state materials.